IMPLEMENTATION OF OBSERVE, CRITICIZE, AND FIX IT (OCF) METHOD IN INCREASING TEACHER'S ABILITY TO ARRANGE QUESTIONS - Risman, Oyong (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by teachers’ ability in arranging questions as an exam outline and the low quality of the questions. Through the Observe, Criticize, and Fix it (OCF) method, it is hoped that teachers’ ability will increase in arranging the questions. This study was an action research conducted at SDN 014 Sidodadi, Logas Tanah Darat District, with 7 teachers as the research subjects. Data were collected through observation sheets and analyzed to see the improvement in teachers’ ability after mentoring with the OCF method. The results of the study showed that in the first cycle, the average percentage of teachers’ abilities was 67.1%, categorized as enough, while in the second cycle it reached 85.4%, which was categorized as good. Based on the results of the study, it can be concluded that the ability of SDN 014 Sidodadi Logas Tanah Darat teachers in arranging questions for exam outlines has increased through the Observe, Criticize, and Fix it (OCF) method.